Utilizing artificial intelligence-based eye tracking technology for screening ADHD symptoms in children - Chen, Xiaolu; Wang, Sihan; Yang, Xiaowen; Yu, Chunmei; Ni, Fang; Yang, Jie; Tian, Yu; Ye, Jiucai; Liu, Hao; Luo, Rong (Frontiers in Psychiatry, 2023)
Objective To explore the potential of using artificial intelligence (AI)-based eye tracking technology on a tablet for screening Attention-deficit/hyperactivity disorder (ADHD) symptoms in children. Methods We recruited 112 children diagnosed with ADHD (ADHD group; mean age: 9.40 ± 1.70 years old) and 325 typically developing children (TD group; mean age: 9.45 ± 1.59 years old). We designed a data-driven end-to-end convolutional neural network appearance-based model to predict eye gaze to permit eye-tracking under low resolution and sampling rates. The participants then completed the eye tracking task on a tablet, which consisted of a simple fixation task as well as 14 prosaccade (looking toward target) and 14 antisaccade (looking away from target) trials, measuring attention and inhibition, respectively. Results Two-way MANOVA analyses demonstrated that diagnosis and age had significant effects on performance on the fixation task [diagnosis: F(2, 432) = 8.231, ***p < 0.001; Wilks’ Λ = 0.963; age: F(2, 432) = 3.999, *p < 0.019; Wilks’ Λ = 0.982], prosaccade task [age: F(16, 418) = 3.847, ***p < 0.001; Wilks’ Λ = 0.872], and antisaccade task [diagnosis: F(16, 418) = 1.738, *p = 0.038; Wilks’ Λ = 0.938; age: F(16, 418) = 4.508, ***p < 0.001; Wilks’ Λ = 0.853]. Correlational analyses revealed that participants with higher SNAP-IV score were more likely to have shorter fixation duration and more fixation intervals (r = −0.160, 95% CI [0.250, 0.067], ***p < 0.001), poorer scores on adjusted prosaccade accuracy, and poorer scores on antisaccade accuracy (Accuracy: r = −0.105, 95% CI [−0.197, −0.011], *p = 0.029; Adjusted accuracy: r = −0.108, 95% CI [−0.200, −0.015], *p = 0.024). Conclusion Our AI-based eye tracking technology implemented on a tablet could reliably discriminate eye movements of the TD group and the ADHD group, providing a potential solution for ADHD screening outside of clinical settings.